Sepsis mortality score for the prediction of mortality in septic patients - Wan Mohd Shukeri, Wan Fadzlina; Md Ralib, Azrina; Abdullah, Norzamzila; Mat Nor, Mohd Basri (Elsevier BV, 2018)
Purpose: To derive a prediction equation for 30-day mortality in sepsis using a multi-marker approach and compare its performance to the Sequential Organ Failure Assessment (SOFA) score. Methods: This study included 159 septic patients admitted to an intensive care unit. Leukocytes count, procalcitonin (PCT), interleukin-6 (IL-6), and paraoxonase (PON) and arylesterase (ARE) activities of PON-1 were assayed from blood obtained on ICU presentation. Logistic regression was used to derive sepsis mortality score (SMS), a prediction equation describing the relationship between biomarkers and 30-day mortality. Results: The 30-day mortality rate was 28.9%. The SMS was [еlogit(p)/(1 + еlogit(p))] × 100; logit(p) =0.74+ (0.004 × PCT)+(0.001 × IL-6)−(0.025 × ARE)−(0.059 × leukocytes count). The SMC had higher area under the receiver operating characteristic curve (95% Cl) than SOFA score [0.814 (0.736–0.892) vs. 0.767 (0.677–0.857)], but is not statistically significant.When the SMSwas added to the SOFA score, prediction of 30-day mortality improved compared to SOFA score used alone [0.845 (0.777–0.899), p=0.022]. Conclusions: A sepsismortality score using baseline leukocytes count, PCT, IL-6 and ARE was derived, which predicted 30-day mortality with very good performance and added significant prognostic information to SOFA score.